Women's Empowerment Model With A Creative Economic Community Approach To Improve Family Welfare In Beringin Village Deli Serdang Regency - Rukmini Rukmini; Mhd Rizaldy Wibowo; Shita Tiara; Nova Azahra; Sri Murniyanti (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
The worsening economic conditions in this new normal era have made the family economy even worse. The prolonged lockdown conditions have limited employment opportunities, while income has decreased. To balance the amount of expenditure and family income, additional family income is needed, in conditions like this, the role of a woman in a family is needed. This study will try to examine and formulate a model of women's empowerment with a creative economy community approach in improving family welfare. Rural women's empowerment activities that will be carried out are providing entrepreneurial motivation, forming business groups, training and business management. Data were collected using observation, interview and questionnaire methods. This research was conducted on village communities, especially housewives in Beringin Village, Beringin District, Deli Serdang Regency. The research used experimental and survey methods. Data analysis techniques used qualitative and quantitative descriptive methods. The outputs of the research are (1) a draft model of women's empowerment with a creative economy community approach in improving family welfare and (2) publication in a national journal with a Technology Readiness Level (TKT) level three. The results of this first year of research are a draft model of women's empowerment. This empowerment model is able to attract the attention of women to actively participate in improving family welfare.